Contextual factors and strategic consequences of cloud Enterprise Resource Planning (ERP) adoption in Malaysian manufacturing SMEs: a conceptual framework - Jayeola, Olakunle; Sidek, Shafie; Abd Rahman, Azmawani; Mahomed, Anuar Shah Bali; Hu, Jimin (International Strategic Management Association, 2020)
Purpose: The purpose of this study is to holistically investigate the interrelationships between key contextual factors of cloud ERP adoption and the strategic consequences of such adoption. Design/Methodology/Approach: The key contextual factors whose influences are explored on cloud ERP adoption are Feature task-match, (FTM); Top Management Support on Change Management (TMSCM) and Government Financial Support (GFS) while the strategic consequences of cloud ERP adoption investigated are competitive advantage (CA) and organisational performance. A conceptual framework grounded in Technology-Organisation-Environment (TOE) model, Task technology-fit (TTF) model and Resource-Based View (RBV) theory is developed for empirical validation that will involve a projected sample of 382 respondents of SMEs in Malaysia using PLS-SEM as main statistical analysis tool. Practical Implications: Practically, this study will guide SMEs' managers on cloud ERP selection that fits their firms' tasks, how to effectively deal with resistance to change occasioned by technology adoption and how effective GFS has been influencing cloud ERP adoption. In addition, SMEs managers stand to gain insight into how cloud ERP adoption can simultaneously and/or indirectly lead to competitive advantage and organisational performance as strategic benefits. Originality/Value: Investigation of a new variant key contextual factors critical for successful cloud ERP adoption and their subsequent impact on CA and organisational performance simultaneously and indirectly.